Application of biomass-based binder in zinc-iodine battery

By using biomass-based binders in zinc-iodine batteries, including components such as carboxymethylcellulose sodium, gelatin and starch, the problem of zinc-iodine batteries is solved, and the problem of poor electrochemical reversibility is achieved, achieving higher energy density and cycle life.

CN119812331APending Publication Date: 2025-04-11ZHEJIANG NORMAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411904662.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Zinc-iodine batteries have severe capacity losses and poor electrochemical reversibility in actual use, which limits their practical application.

Method used

A biomass-based binder, including sodium carboxymethylcellulose, gelatin and starch, is used as the binder for the positive electrode material of zinc-iodine battery, and the electrode material is fixed by chemical bonding to improve the electrode structure and electrochemical performance.

Benefits of technology

It effectively improves the energy density and cycle life of zinc-iodine batteries, inhibits the shuttle effect of iodide, and optimizes battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812331A_ABST
    Figure CN119812331A_ABST
Patent Text Reader

Abstract

The invention discloses application of a biomass-based binder to a zinc-iodine battery, the biomass-based binder comprises a first component, a second component and a third component, the first component is selected from sodium carboxymethyl cellulose (CMC) or carboxymethyl cellulose-citric acid (CMC-CA), the second component is selected from gelatin (GN) or phosphorylated soybean protein-phytic acid polyethylene oxide (SPP), and the third component is selected from sodium carboxymethyl cellulose (CMC-CA) or sodium carboxymethyl cellulose (CMC-CA). And the third component is selected from starch (ST), beta-cyclodextrin (beta-CD) or crown ether. The biomass-based binder provided by the invention can improve the fixation of a positive electrode material and enhance the stability of an electrode structure, so that the energy density and the service cycle life of the zinc-iodine battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the application field of zinc-iodine battery materials and the application field of positive electrode material binders, and specifically relates to the application of a biomass-based binder in zinc-iodine batteries. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in portable electronic devices, electric vehicles, and energy storage due to their advantages such as high energy density, long cycle life, low self-discharge rate, and no memory effect. However, lithium ions have poor thermal stability of electrolytes, and the electrolytes are easily decomposed to produce gas and oxygen. Therefore, zinc-ion batteries use zinc as the anode, which has abundant natural resources, low redox potential (-0.76V compared to the standard hydrogen electrode), and high theoretical capacity (820mAh g -1 and 5855mAh cm -3 ) and other advantages, and is one of the most promising alternatives. Rechargeable metal iodine batteries have the advantages of high theoretical specific capacity, high abundance, low cost, and good redox reversibility of iodine, and are expected to become an alternative energy storage system. In particular, Zn-I2 batteries show obvious advantages due to the fast redox chemical reaction of metallic zinc and iodine in mild aqueous solution and intrinsic safety. However, the shuttling effect of soluble polyiodides leads to severe capacity loss and poor electrochemical reversibility, which limits their practical use.

[0003] The methods currently used in the prior art are:

[0004] A Chinese patent with publication number CN116826314A discloses a zinc-iodine battery separator and a preparation method thereof. The zinc-iodine battery separator is prepared by coating the positive electrode slurry prepared by single-walled carbon nanotubes modified with iron nanoparticles, an aqueous mixture of a carbon tube binder and deionized water in a mass ratio of 1:35:24 on the positive electrode side, and a negative electrode slurry prepared by a commercial cation exchange resin, 2% sodium carboxymethyl cellulose and 40% styrene-butadiene rubber in a mass ratio of 34:250:2.5 on the negative electrode side of a commercial glass fiber separator using a coating rod, and then drying at room temperature. The zinc-iodine battery separator provided by the invention can inhibit the side reaction at the zinc negative electrode interface to allow zinc to be uniformly deposited, weaken the shuttling effect of polyiodide at the iodine positive electrode interface and the redox kinetics of catalytic iodine species, and enable the zinc-iodine battery to achieve an ultra-long cycle of 30,000 cycles. The Chinese patent with publication number CN118630341A discloses a degradable water-based biomass zinc-iodine battery and a preparation method thereof, comprising an iodine positive electrode, a zinc negative electrode, a battery separator, an electrolyte solution, and an electrolyte solution additive; the iodine positive electrode is a mixed material prepared by mixing activated carbon, a polyiodide ion fixing agent, an iodine element, a conductive material, and a binder in a mass ratio of (7.5-8.5):(3.5-4.5):(3.5-4.5):(0.75-1.5):(0.75-1.25); the electrolyte solution is a concentrated The concentration of the zinc chloride aqueous solution is 1-5M; the electrolyte solution additive is sodium alginate colloid; the battery separator is wood cellulose; the invention adopts a mixed material of polyiodide ion fixative and activated carbon in the positive electrode, which can enhance the adsorption of iodine by the positive electrode and increase the battery capacity per unit area; sodium alginate is added to the electrolyte to inhibit dendrites; wood cellulose carbon cloth is used as the battery separator to replace the original traditional difficult-to-degrade material, which not only greatly improves the recyclability of the battery, but also effectively reduces the shuttle effect of iodine and optimizes the battery performance.

[0005] As an inactive component in zinc-iodine battery electrode sheets, binder is one of the important materials for preparing zinc-iodine battery electrode sheets. The main function of the binder is to connect the electrode active material, the conductive agent and the electrode current collector so that they have overall connectivity. In addition, the binder also provides mechanical adhesion for the active material and the conductive additive. Although traditional binders such as polyvinylidene fluoride (PVDF) perform well in lithium-ion batteries, they have disadvantages in zinc-iodine batteries such as high cost, complex processing, and limited improvement on the dissolution problem of polyiodide.

[0006] Therefore, how to solve the above-mentioned technical problems of zinc-iodine batteries through more effective binders has become the focus of current research. Summary of the invention

[0007] The purpose of the present invention is to provide an application of a biomass-based binder in a zinc-iodine battery, which can improve the fixation of its positive electrode material and enhance the stability of the electrode structure, thereby improving the energy density and service cycle life of the zinc-iodine battery.

[0008] The present invention provides the following technical solutions:

[0009] The invention discloses an application of a biomass-based binder in a zinc-iodine battery. The biomass-based binder comprises a first component, a second component and a third component. The first component is selected from sodium carboxymethyl cellulose (CMC) or carboxymethyl cellulose-citric acid (CMC-CA), the second component is selected from gelatin (GN) or phosphorylated soy protein-phytic acid polyethylene oxide (SPP), and the third component is selected from starch (ST), β-cyclodextrin (β-CD) or crown ether.

[0010] The biomass-based binder provided by the present invention, when used as a positive electrode material binder for an aqueous zinc-iodine battery, promotes the penetration of electrolytes and the transmission of ions, and simultaneously effectively fixes the electrode material through chemical bonding, promotes charge transfer and improves the electrode structure, and effectively inhibits iodide shuttling, thereby further improving the performance and cycle stability of the zinc-iodine battery: CMC and CMC-CA have chemical adsorption and adhesive effects, gelatin and phosphorylated soybean protein-phytic acid polyethylene oxide play catalytic and adhesive roles, and β-CD, crown ether, and ST have physical adsorption and fixation effects; and the raw materials are not only low-cost and environmentally friendly, but also have good film-forming properties and biocompatibility, and are particularly suitable for fixing the positive electrode material of the zinc-iodine battery and enhancing the stability of the electrode structure.

[0011] Preferably, the biomass-based binder comprises sodium carboxymethyl cellulose, gelatin and starch.

[0012] Preferably, the biomass-based binder comprises sodium carboxymethylcellulose, gelatin and β-cyclodextrin.

[0013] Preferably, the biomass-based binder includes sodium carboxymethyl cellulose, phosphorylated soy protein-phytic acid polyethylene oxide and crown ether.

[0014] Preferably, the biomass-based binder comprises carboxymethyl cellulose-citric acid, gelatin and starch.

[0015] Preferably, the mass ratio of the first component, the second component and the third component is 10:1-10:1-10.

[0016] As further preferred, the mass ratio of the first component, the second component and the third component is 10:2-5:2-5.

[0017] As further preferred, the first component is sodium carboxymethyl cellulose, the second component is gelatin, the third component is starch or β-cyclodextrin, and the mass ratio of the first component, the second component and the third component is 10:5:2-5.

[0018] Preferably, the zinc-iodine battery comprises an iodine electrode, and the iodine electrode comprises activated carbon adsorbing iodine, superconducting carbon black and a biomass-based binder.

[0019] The preparation method of the biomass-based binder includes: dissolving a first component, a second component and a third component in deionized water, dissolving them in hot water at 50 degrees, and finally obtaining a biomass-based binder; mixing activated carbon adsorbed iodine, superconducting carbon black and the binder, uniformly coating them on carbon paper with a diameter of 1 cm, and drying them in a vacuum oven at 80 degrees Celsius for 12 hours to obtain an iodine electrode.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The biomass-based binder raw material provided by the invention is low in price, the method is simple and the repeatability is high. The battery assembled by combining the material as the positive electrode material of the aqueous zinc-iodine battery with a zinc sheet can provide a higher energy density and a longer battery cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The morphology of the positive electrode coated with CMC, GN and ST prepared in Example 1 was observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM).

[0023] Figure 2 The morphology of the positive electrode coated with CMC, GN and β-CD prepared in Example 2 was observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM).

[0024] Figure 3 The morphology of the positive electrode coated with CMC, SPP and crown ether prepared in Example 3 was observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM).

[0025] Figure 4 The morphology of the positive electrode coated with CMC-CA, GN and ST prepared in Example 4 was observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM).

[0026] Figure 5 The morphology of the positive electrode coated with CMC-CA, SPP and crown ether prepared in Comparative Example 1 was observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM).

[0027] Figure 6 The morphology of the positive electrode coated with PVDF prepared in Comparative Example 2 was observed using a Hitachi S-4800 field emission scanning electron microscope (FE-SEM).

[0028] Figure 7 The constant current charge-discharge curves of the button cells with CMC, GN and ST as positive electrode materials in Example 1 were tested by the CT3001A electrochemical workstation of Wuhan Blue Electric Company.

[0029] Figure 8 The constant current charge-discharge curves of the button cells with CMC, GN and β-CD binders as positive electrode materials in Example 2 were tested by the CT3001A electrochemical workstation of Wuhan Blue Electric Company.

[0030] Fig. 9 The constant current charge-discharge curves of the button cells with CMC, SPP and crown ether binder as positive electrode materials in Example 3 were tested by the CT3001A electrochemical workstation of Wuhan Blue Electric Company.

[0031] Fig.10 The constant current charge-discharge curves of the button cells with CMC-CA, GN and ST binders as positive electrode materials in Example 4 were tested by the CT3001A electrochemical workstation of Wuhan Blue Electric Company.

[0032] Fig.11 The constant current charge and discharge curves of the button cells with CMC-CA, SPP and crown ether binder as positive electrode materials in Comparative Example 1 were tested by the CT3001A electrochemical workstation of Wuhan Blue Electric Company.

[0033] Fig.12 The constant current charge and discharge curve of the button battery with PVDF binder as the positive electrode material in Comparative Example 2 was tested by the CT3001A electrochemical workstation of Wuhan Blue Electric Company.

[0034] Fig.13 The rate performance curves of the button cells with CMC, GN and ST as positive electrode materials in Example 1 were tested by the CT3001A electrochemical workstation of Wuhan Blue Electric Company.

[0035] Fig.14 The rate performance curve of the button cell with CMC, GN and β-CD binder as the positive electrode material in Example 2 was tested by the CT3001A electrochemical workstation of Wuhan Blue Electric Company.

[0036] Fig.15 The rate performance curve of the button cell using CMC, SPP and crown ether binder as positive electrode materials in Example 3 was tested by the CT3001A electrochemical workstation of Wuhan Blue Electric Company.

[0037] Fig.16 The rate performance curves of the button cells using CMC-CA, GN and ST binders as positive electrode materials in Example 4 were tested by the CT3001A electrochemical workstation of Wuhan Blue Electric Company.

[0038] Fig.17The rate performance curve of the button cell with CMC-CA, SPP and crown ether binder as positive electrode materials in Comparative Example 1 was tested by CT3001A electrochemical workstation of Wuhan Blue Electric Company.

[0039] Fig.18 The rate performance curve of the button battery with PVDF binder as the positive electrode material in Comparative Example 2 was tested by the CT3001A electrochemical workstation of Wuhan Blue Electric Company. DETAILED DESCRIPTION

[0040] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.

[0041] Example 1

[0042] 10g CMC, 5g GN and 5g ST binder were dissolved in deionized water and dissolved in 50 degrees hot water to prepare a binder. Then, activated carbon adsorbed iodine, superconducting carbon black and the binder were mixed and evenly coated on a carbon paper with a diameter of 1cm, and dried in a vacuum oven at 80℃ for 12h to obtain an iodine electrode.

[0043] The SEM of the obtained product is shown in Figure 1 , it can be observed that the binder microstructure of CMC-GN-ST adhesive is smooth and has no cracks.

[0044] Example 2

[0045] 10g CMC, 5g GN and 2g β-CD binder were dissolved in deionized water and dissolved in 50 degrees hot water to prepare a binder. Then, activated carbon adsorbed iodine, superconducting carbon black and the binder were mixed and evenly coated on a carbon paper with a diameter of 1cm, and dried in a vacuum oven at 80℃ for 12h to obtain an iodine electrode.

[0046] The SEM of the obtained product is shown in Figure 2 , it can be observed that the binder microstructure of CMC-GN-β-CD adhesive is smooth and has no cracks.

[0047] Example 3

[0048] 10g CMC, 5g SPP and 3g crown ether binder were dissolved in deionized water and dissolved in 50 degrees hot water to prepare a binder. Then, activated carbon adsorbed iodine, superconducting carbon black and the binder were mixed and evenly coated on a carbon paper with a diameter of 1cm, and dried in a vacuum oven at 80℃ for 12h to obtain an iodine electrode.

[0049] The SEM of the obtained product is shown in Figure 3, it can be observed that the binder microstructure of CMC-SPP-crown ether binder is smooth and has no cracks.

[0050] Example 4

[0051] 10g CMC-CA, 2g GN and 5g ST binder were dissolved in deionized water and dissolved in 50 degrees hot water to prepare a binder. Then, activated carbon adsorbed iodine, superconducting carbon black and the binder were mixed and evenly coated on a carbon paper with a diameter of 1cm, and dried in a vacuum oven at 80℃ for 12h to obtain an iodine electrode.

[0052] The SEM of the obtained product is shown in Figure 4 , it can be observed that the binder microstructure of CMC-CA-GN-ST adhesive is smooth and has no cracks.

[0053] Comparative Example 1

[0054] 10g CMC-CA, 4g SPP and 5g crown ether binder were dissolved in deionized water and dissolved in 50 degrees hot water to prepare a binder. Then, activated carbon adsorbed iodine, superconducting carbon black and the binder were mixed and evenly coated on a carbon paper with a diameter of 1cm, and dried in a vacuum oven at 80℃ for 12h to obtain an iodine electrode.

[0055] The SEM of the obtained product is shown in Figure 5 , it can be observed that the binder microstructure of CMC-CA-SPP-crown ether binder is smooth and has no cracks.

[0056] Comparative Example 2

[0057] 10g of PVDF binder was dissolved in deionized water and dissolved in hot water at 50 degrees to prepare a binder. Then, activated carbon adsorbed iodine, superconducting carbon black and the binder were mixed and evenly coated on a carbon paper with a diameter of 1cm, and dried in a vacuum oven at 80°C for 12h to obtain an iodine electrode.

[0058] The SEM of the obtained product is shown in Figure 6 , it can be observed that the binder microstructure of GNSA adhesive is flat but has cracks.

[0059] Application Examples

[0060] Electrochemical testing

[0061] The material obtained in Example 1 was applied to electrochemical tests, and all electrochemical tests were completed in button cells.

[0062] Take the material prepared in Example 1, cut it into electrode sheets using a cutting machine, use it as the positive electrode, zinc foil as the negative electrode, and 2M Zn2SO4 as the electrolyte to assemble a button battery.

[0063] The specific capacity performance test of Examples 1 to 4 was carried out. Figures 7-10 As shown: From the current density of 0.2A g -1 To 10Ag -1 Among them, Example 1 has the best performance, and its maximum specific capacitance performance is 189.0 mAh g -1 Example 2, the maximum specific capacitance performance is 178.3mAh g -1 Example 3, the maximum specific capacitance performance is 176.7mAh g -1 Example 4, the maximum specific capacitance performance is 141.5mAh g -1 ;

[0064] The specific capacity performance test was carried out on Comparative Examples 1 and 2. Figures 11-12 As shown in: Comparative Example 1, its maximum specific capacitance performance is 134.9 mAh g -1 Comparative Example 2, its maximum specific capacitance performance 131.0mAh g -1 ;

[0065] The rate performance test was carried out on Examples 1 to 5. Figures 12 to 16 As shown: At a current density of 0.2A g -1 Up to 10A g -1 At this current, after 40 cycles, the specific capacity of Example 1 decreased by 62.5 mAh g -1 , at a current density of 0.2Ag -1 The specific capacity remains at 170 mAh g -1 ; Example 2 specific capacity decreased by 63.5 mAhg -1 At a current density of 0.2A -1 The specific capacity remains at 130 mAh g -1 ; The specific capacity of Example 3 decreased by 55.0 mAh g -1 , at a current density of 0.2Ag -1 The specific capacity remains at 127 mAh g -1 ; Example 4 specific capacity decreased by 59.0 mAh g -1 , at a current density of 0.2Ag -1 The specific capacity remains at 127 mAh g -1 ;

[0066] The rate performance test was performed on Comparative Example 1. Figures 17-18 As shown: the specific capacity of comparative example 1 decreased by 40.0 mAhg -1 , at a current density of 0.2Ag -1 The specific capacity is maintained at 137 mAh g -1 ; The specific capacity of comparative example 2 decreased by 60.0 mAh g-1 , at a current density of 0.2Ag -1 The specific capacity is maintained at 127 mAh g -1 ;

[0067] The above results show that the biobinder prepared in Examples 1-4 has a high specific capacity, and the material is applied to zinc-iodine batteries, which has good energy density and excellent rate performance. The present invention promotes the research of CMC-GN-ST binder, CMC-GN-β-CD binder, CMC-SPP-crown ether binder and CMC-CA-GN-ST binder on zinc-iodine batteries, which plays a certain role in promoting the development of zinc ion energy storage with high cycle performance.

Claims

1. Application of a biomass-based binder in a zinc-iodine battery, characterized in that: The biomass-based binder comprises a first component, a second component and a third component. The first component is selected from sodium carboxymethylcellulose or carboxymethylcellulose-citric acid, the second component is selected from gelatin or phosphorylated soy protein-phytic acid polyethylene oxide, and the third component is selected from starch, beta-cyclodextrin or crown ether.

2. The use according to claim 1, characterized in that: The biomass-based binder includes sodium carboxymethylcellulose, gelatin and starch.

3. The use according to claim 1, characterized in that: The biomass-based binder includes sodium carboxymethylcellulose, gelatin and β-cyclodextrin.

4. The use according to claim 1, characterized in that: The biomass-based binder includes carboxymethylcellulose-citric acid, gelatin and starch.

5. The use according to claim 1, characterized in that: The biomass-based binder includes carboxymethyl cellulose-citric acid, phosphorylated soybean protein-phytic acid polyethylene oxide and crown ether.

6. The use according to any one of claims 1 to 5, characterized in that: The mass ratio of the first component, the second component and the third component is 10:1-10:1-10.

7. The use according to claim 6, characterized in that: The mass ratio of the first component, the second component and the third component is 10:2-5:2-5.

8. The use according to claim 6, characterized in that: The first component is sodium carboxymethyl cellulose, the second component is gelatin, and the third component is starch or beta-cyclodextrin. The mass ratio of the first component, the second component and the third component is 10:5:2-5.

9. The use according to claim 6, characterized in that: The zinc-iodine battery comprises an iodine electrode, wherein the iodine electrode comprises activated carbon adsorbing iodine, superconducting carbon black and a biomass-based binder.

Citation Information

Patent Citations

  • Zinc-iodine battery diaphragm and battery thereof

    CN116826314A

  • Degradable aqueous biomass zinc-iodine battery and preparation method thereof

    CN118630341A

  • Modified biomass lithium ion battery adhesive

    CN103337656A

  • Lithium ion selenium battery with long service life

    CN103700820A

  • Vanadium-based lithium-insertion material / sulfur composite positive electrode and preparation method and application thereof

    CN105322131A